FLEXURAL STRENGTH OF PINEAPPLE LEAF FIBER REINFORCED METAKAOLIN ZIRCONIA CARBONATE APATITE GEOPOLYMER COMPOSITE - Andrie Harmaji; Susanti Nurfadhila; Bambang Sunendar (Jurnal Teknologi, 2023)
Developments in the materials engineering have encouraged the incorporation of minerals such as kaolin, zirconia, and carbonate apatite, and natural materials. Indonesia, which has a tropical climate, is overgrown with pineapple plants. Geopolymer is a brittle ceramic material so it is necessary to increase its flexural strength value for composite application. Pineapple leaf fiber can be used as reinforcement in geopolymer composites. This study aims to analyze the effect of adding pineapple leaf fiber (Ananas comosus (L.) Merr.) to the mechanical properties and morphological characteristics of metakaolin-zirconia-carbonate apatite-based geopolymer composites. The use of chitosan coupling agent as a binder between the matrix and filler. The research sample consisted of 4 groups with a total of 5 samples in each group. Fiber varied 0-4% in Geopolymer Composites. Geopolymer Composite samples were tested for flexural strength and Scanning Electron Microscope (SEM). The test results showed that the addition of pineapple leaf fiber increased the flexural strength of the geopolymer composite. The composite without the addition of fiber had a flexural strength of 11.24 MPa, while the addition of 1%, 2.5%, and 4% pineapple fiber resulted in a flexural strength of 20.71 MPa, 11.57 MPa, and 11.01 MPa. The results of the SEM test show a picture of the void with varying sizes. The SEM Images of composite with the addition of 4% pineapple fiber showed the formation of Na2CO3 which explained the decrease in flexural strength compared to the sample without pineapple fiber addition.